Molecular causes of sex‐specific deficits in rodent models of neurodevelopmental disorders. Issue 1 (23rd December 2019) - Mossa, Adele; Manzini, M. Chiara
Abstract: Neurodevelopmental disorders (NDDs) such as intellectual disability and autism spectrum disorder consistently show a male bias in prevalence, but it remains unclear why males and females are affected with different frequency. While many behavioral studies of transgenic NDD models have focused only on males, the requirement by the National Institutes of Health to consider sex as a biological variable has promoted the comparison of male and female performance in wild‐type and mutant animals. Here, we review examples of rodent models of NDDs in which sex‐specific deficits were identified in molecular, physiological, and/or behavioral responses, showing sex differences in susceptibility to disruption of genes mutated in NDDs. Haploinsufficiency in genes involved in mechanisms such as synaptic function ( GABRB3 and NRXN1 ), chromatin remodeling ( CHD8, EMHT1, and ADNP ), and intracellular signaling ( CC2D1A and ERK1 ) lead to more severe behavioral outcomes in males. However, in the absence of behavioral deficits, females can still present with cellular and electrophysiological changes that could be due to compensatory mechanisms or differential allocation of molecular and cellular functions in the two sexes. By contrasting these findings with mouse models where females are more severely affected ( MTHFR and AMBRA1 ), we propose a framework to approach the study of sex‐specific deficits possibly leading to sex bias in NDDs.